Shared Creative Space Intervention: Enhancing Collaborative Behavior among Rattan Artisans in Pekanbaru - Dea Amanda; Ratna Amanati; Wahyu Hidayat (Program Studi Arsitektur, Fakultas Teknik, Universitas Riau, 2026)
The creative rattan handicraft industry in Pekanbaru faces significant physical infrastructure constraints due to rigid, top-down conventional design approaches. Current workspaces are unrepresentative of dynamic production workflows, which decreases productivity and neglects intergenerational local knowledge transfer. This study aims to formulate a participatory architecture framework for the design of a community-based, adaptive Creative Rattan Workshop in Pekanbaru. This study employs a descriptive-qualitative method through a structured literature review on spatial flexibility and responsive architecture, combined with a comparative analysis of creative industry building precedents. The analysis demonstrates that integrating the Participatory Rural Appraisal (PRA) method in the design phase successfully transforms artisans into active co-designers. The synthesis yields five core spatial strategies: active artisan involvement, the application of the six-stage PRA method, the utilization of flexible architectural elements (modular furniture and non-permanent partitions), layout zoning based on actual operational sequences, and the provision of social communal spaces. The application of participatory architecture is proven effective not only in generating ergonomic physical infrastructure that flexes with production volumes but also in fostering a profound sense of community ownership while sustainably preserving the collective memory of the local rattan craft.